(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Ayurveda is an ancient science dealing with attaining health and curing diseases of ill. Good health makes our life happy. For that one has to take Wholesome of food which includes pure water also. We should always use the pure water to maintain health. Our Rishis have mentioned regarding Hansodaka in Samhitas. Hansodaka is purified water in Sharad ritu by natural resources like Sunrays, Moonrays and an additional effects of Agasti star rays at night and Kalprabhav of Sharad ritu. This Hansodaka is pure water and ideal for drinking purpose. So to check this statement of our Rishis, efforts are made here to compare such Hansodaka and simple Tadagjal in view of chemical properties, considering W.H.O. guideline in present era. Aims and Objective: To compare chemical properties of Simple Tadagjal and Hansodaka to check its suitability for drinking purpose. Materials and Methods: Total four samples were collected. Two were Simple Tadadjal and Two were Hansodaka. All Water samples were analyzed in standard laboratory for chemical properties. Reports were collected and analyzed. Results and Conclusion: Hansodaka is better than simple Tadagjal with respect to chemical properties. It may be due to combine effect of sunrays, moon rays and Agasti star rays in Sharad ritu. But Hansodaka is not suitable for drinking purpose as per W.H.O. guideline. it may be due to increased population, pollution, industrialization in present era as compared to ancient era. Hence we can say water purification by other methods is must in present era.